2017
DOI: 10.21873/anticanres.11375
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Epidermal Growth Factor Receptor Mutation in Smokers with Lung Cancer Without Pulmonary Emphysema

Abstract: Abstract. Background: Chronic obstructive pulmonary disease is a smoking-related disease, and is categorized into the emphysema and airway dominant phenotypes. We examined the relationship between emphysematous changes and epidermal growth factor receptor (EGFR) mutation (Odds Ratio=3.47, p=0.005). Conclusion: Our data showed a relationship between emphysematous changes and EGFR mutation status. There might be mutually exclusive genetic risk factors for carcinogenesis and development of emphysematous changes.L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Down regulation of c-Myc is associated with invasion/migration capacity of bronchial epithelial cells exposed to cigarette smoke extract 147 . EGFR 95 mutations act an oncogenic driver of lung cancer in non-smokers and light smokers 148 150 .…”
Section: Discussionmentioning
confidence: 99%
“…Down regulation of c-Myc is associated with invasion/migration capacity of bronchial epithelial cells exposed to cigarette smoke extract 147 . EGFR 95 mutations act an oncogenic driver of lung cancer in non-smokers and light smokers 148 150 .…”
Section: Discussionmentioning
confidence: 99%
“…Importantly even in non-smoking patients, the EGFR mutation rate in patients with COPD was significantly lower than those without COPD ( p = 0.001). Another study led by Takeda et al showed 25% EGFR mutation in lung cancer without emphysema and 9% in those with emphysema [23]. As active EGFR mutation is the critical factor to predict the response and survival outcome for patients that underwent EGFR-TKI treatment, it is unsurprisingly that COPD patients might had poor treatment efficacy on EGFR-TKI because of inherited low EGFR mutation frequency [24].…”
Section: Discussionmentioning
confidence: 99%
“…But in cancer cells these two proteins experience changes characteristics due to changes in the structure of the constituent amino acids. 9 EGFR mutations include the type of point, deletion, and insertion mutations that occur most frequently on exons 18,29,20 and 21. 10 EGFR examination is one way to provide appropriate therapy for Non Small Cell Lung Carcinoma (NSCLC) sufferers.…”
Section: Introductionmentioning
confidence: 99%